Probability analysis of occupational accidents in housing construction projects using the hazop method: A risk-based approach to safety performance improvement - Shafiudin, Muhammad; Prayoga, Celvin Setya; Firmanda, Richo Alivyan; Juliawan, Ferdika Rahmad; Septian, Robertus Yunico (Calamity: A Journal of Disaster Technology and Engineering, 2025)
Background: In construction work, occupational accidents remain one of the most critical issues in the construction industry, particularly in housing development projects that involve various high-risk activities. An occupational accident is an undesired and unexpected event that occurs in the workplace, resulting in worker injuries, equipment damage, workflow disruption, or even fatalities. Methods: This study aims to analyze the probability of work accidents using the Hazard and Operability Study (HAZOP) approach to identify potential hazards and operational failures in each stage of construction work at the XYZ housing project. The method is applied to systematically review various risk scenarios based on field observations, interviews, and available safety documentation. Findings: The HAZOP analysis successfully identified six critical hazards in the XYZ housing development project, including material-related accidents, falls from heights, heavy material intrusion, and respiratory disorders from dust, primarily caused by worker negligence, lack of proper procedures, and inadequate use of PPE. Conclusion: The implementation of integrated preventive measures such as the provision of complete PPE, structured SOP development, continuous training, and strict supervision has proven to be an effective strategy in mitigating occupational accident risks in construction environments. Novelty/Originality of this article: This study presents a systematic HAZOP-based approach combined with the 5S methodology and enhanced SOP enforcement as a practical and replicable model for risk evaluation in residential construction projects.